The Impact of Heat Input on the Microhardness and the Micro-structure of a Welded Carbon Steel and the Modeling of its Micro-crack - Mbelle Samuel Bisong; Kevin Tsapi Tchoupou; Valeriy V. Lepov; Kisito Pierre (Current Approaches in Engineering Research and Technology Vol. 2, 2024)
The welding process induces changes in the Heat-Affected Zone (HAZ) owing to thermal effects. This implies alterations in mechanical properties and microstructure based on the magnitude of absorbed heat and cooling time. The analysis presented in this article reveals that the base metal, initially composed of ferrite and pearlite, undergoes a change in grain size after welding. During welding, the heat produced during the process can affect the microhardness and the microstructure of the material. The change in the microstructure and the microhardness can be discovered by carrying out a microhardness test on the welded sample and comparing changes in the three different zones i.e the base, the weld and the Heat affected zone (HAZ), or by carrying out a microstructural examination on the welded sample and see the grain dispersion in relation to their sizes. In this work, the weld quality of manual arc welded samples of low-carbon steel St3sp destined for bridge construction to be used in Cameroon has been investigated. After a chemical analysis of the material, a microhardness test and a microstructural examination were also done. Results show that a composition of pearlite and ferrite was seen with a composition of 20/80 respectively. For weld zone and HAZ it changes due to thermal processes. So the micro-structure analysis shows that the base metal is a ferrite and pearlite having a grain size of 11-12 on a scale corresponding to an average grain diameter \(≈\)of 7 microns. The structure of the weld metal is also made up of ferrite and pearlite with columnar crystals of cast metal. The HAZ is made up of Widmanstätten. The width of the HAZ zone is about 1,5mm in different areas of heat affected zone and is observed fine-grained ferrite-pearlite structure with a high degree of dispersion. A micro-crack was revealed with a length of 1,7 mm in the HAZ of sample number 7 and a 1,2 mm length of micro-crack in the weld zone of this same probe was also revealed. The modeling of the micro-crack shows that the velocity of its propagation in the welded zone is higher as much than that in the heat-affected zone i.e. in the welded zone is estimated at 64.59m/s, while in heat affected zone is 0,354.1 m/s. This means that in the absence of welded and environmental defects, failure of structure will be common in the welded zone.